Coherent control of ultrafast bond making and subsequent molecular dynamics: Demonstration of final-state branching ratio control - Levin, Liat; Reich, Daniel M.; Geva, Moran; Kosloff, Ronnie; Koch, Christiane; Amitay, Zohar (Journal of Physics B: Atomic, Molecular and Optical Physics, 2021)
Quantum coherent control of ultrafast bond making and the subsequent molecular dynamics is crucial for the realization of a new photochemistry, where a shaped laser field is actively driving the chemical system in a coherent way from the thermal initial state of the reactants to the final state of the desired products. We demonstrate here coherent control over the relative yields of Mg2 molecules that are generated via photoassociation and subsequently photodriven into different groups of final states. The strong-field process involves non-resonant multiphoton femtosecond photoassociation of a pair of thermally hot magnesium atoms into a bound Mg2 molecule and subsequent molecular dynamics on electronically excited states. The branching-ratio control is achieved with linearly chirped laser pulses, utilizing the different chirp dependence that various groups of final molecular states display for their post-pulse population. Our joint experimental and theoretical study establishes the feasibility of high degree coherent control over quantum molecular dynamics that is initiated by femtosecond photoassociation of thermal atoms.
CRIS-Team Scopus Importer:2023-04-20
Keywords: coherent control; coherent control of bond making; femtosecond coherent control; quantum coherent control; ultrafast bond making